There is a Critical Relationship Between Discourse Delay and Cerebral Paralysis in Cerebral Palsy Child Patients at Haji Medan Hospital in 2023 - Armand Surya Nugraha; Nurcahaya Sinaga (Buletin Farmatera, 2025)
Abstract: Speech delay in children can be a condition in which the child's expressive dialect development is inappropriate or underage. The frequency of speech delay in Indonesian children who do not attend school reaches 5–10%. Boys with speech disorders more than girls. The cause of speech delay can be hearing loss, cerebral palsy, low thinking ability, or autism. Cerebral palsy patients can experience wild movements and muscle spasms in the mouth. This will affect the child's speech development. This study aims to find out if there is a critical relationship between discourse delay and cerebral palsy in pediatric patients at Haji Medan Hospital in 2023. This research is an analytical descriptive research with a cross-sectional approach. The subjects of this study are cerebral palsy patients at Haji Medan Hospital, with an estimated total test of 132 people. Data analysis using Chi-square test. There is a significant relationship between speech delay and cerebral palsy in pediatric patients at Haji Medan Hospital. The results using Fisher's correct test showed a P value of less than 0.05, which supports the theory. There is a critical relationship between delay in discourse and cerebral palsy in pediatric patients at Haji Medan Hospital.